2020
DOI: 10.1089/jir.2020.0111
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interleukin-6 Inducible Gene PDZ-Binding Kinase Promotes Tumor Growth of Multiple Myeloma Cells

Abstract: Multiple myeloma (MM) remains an intractable hematological malignancy, despite recent advances in anti-MM drugs. Here, we show that role of PDZ binding kinase (PBK) in MM tumor growth. We identified that interleukin-6 (IL-6) readily increases PBK expression. Kaplan–Meier analysis showed that the MM patients with higher expression of PBK have a significant shorter survival time compared with those with moderate/lower expression of PBK. Knockout of PBK dramatically suppressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
0
12
2
Order By: Relevance
“…In contrast to reports in malignant tumors such as multiple myeloma in which PBK enhances the malignant potential of tumor cells and is associated with unfavorable clinical outcome ( Brown-Clay et al, 2015 ; Kwon et al, 2016 ; Ohashi et al, 2016 ; Ohashi et al, 2017 ; Yang et al, 2017 ; Ota et al, 2020 ), our study revealed favorable survival of CRC patients with PBK-high tumors ( Nagano-Matsuo et al, 2021 ). PBK showed a significant positive association with Ki-67, a widely used cellular proliferation marker, along with a significant inverse association to pT stage in CRC ( Nagano-Matsuo et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to reports in malignant tumors such as multiple myeloma in which PBK enhances the malignant potential of tumor cells and is associated with unfavorable clinical outcome ( Brown-Clay et al, 2015 ; Kwon et al, 2016 ; Ohashi et al, 2016 ; Ohashi et al, 2017 ; Yang et al, 2017 ; Ota et al, 2020 ), our study revealed favorable survival of CRC patients with PBK-high tumors ( Nagano-Matsuo et al, 2021 ). PBK showed a significant positive association with Ki-67, a widely used cellular proliferation marker, along with a significant inverse association to pT stage in CRC ( Nagano-Matsuo et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Several PBK-targeting compounds such as HI-TOPK-032, SKLB-C05 and Ginsenoside Rh2 have been reported to suppress tumor growth and/or metastasis of CRC ( Gao et al, 2019 ; Yang et al, 2016 ; Kim et al, 2012 ). Our group successfully inhibited the growth of multiple myeloma and CRC cells using OTS514, a specific PBK inhibitor ( Figures 2C,D ) ( Ota et al, 2020 ; Nagano-Matsuo et al, 2021 ). OTS514 not only suppressed the cellular proliferation of CRC cells but it also induced apoptosis with down-regulation of PHH3.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PDZK1 is overexpressed in MM cell lines and drives resistance to chemotherapy in vitro 50 . Although this has been largely underexplored, a recent study showed that PDZ binding kinase is induced by IL-6 and promotes growth through STAT3 pathway 51 , yet another example of a protein at the 1q21 locus that is involved in the IL6-STAT3 continuum. PSMD4 and ILF2 have been implicated in resistance to specific treatments and are summarized later in the review.…”
Section: Potential Genetic Drivers On Chromosome 1qmentioning
confidence: 99%
“…9 Furthermore, it has been reported that inhibiting TOPK by specific inhibitors, OTS514 and OTS964, effectively inhibits the proliferation of many tumour cells. [30][31][32][33] Clinical studies reported that the expression of TOPK was strongly associated with poor prognosis of cancer patients. [34][35][36] As a potential tumour marker, TOPK has attracted extensive attention from basic and clinical researchers.…”
Section: Discussionmentioning
confidence: 99%